How Predictable is the Chinese Stock Market? - JIANG, Fuwei (Institutional Knowledge at Singapore Management University, 2011)
We analyze return predictability for the Chinese stock market index and its components sorted on industry, size, book-to-market and ownership concentration, with both in-sample and out-of-sample tests. We find significant predictability. Among industry portfolios, Finance and insurance, Real estate, and Manufacturing exhibit the most predictability, while small-cap, low book-to-market ratio and low ownership concentration firms also display considerable predictability. The conditional CAPM model largely accounts for component predictability, and industry concentration significantly explain differences in return predictability across industries, consistent with the information-flow frictions emphasized by Hong, Torous, and Valkanov (2007).